1988
DOI: 10.1002/jmv.1890250106
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lymphoproliferative responses to rotavirus

Abstract: In comparison with healthy adults, elderly patients and patients who had received renal transplants had significantly lower lymphoproliferative responses to rotavirus (P = 0.04, P = 0.002, respectively) and phytohaemagglutinin (P = 0.001). However, following acute rotavirus infection, elderly persons mounted good lymphoproliferative and specific antibody responses to rotavirus. No lymphoproliferative response or specific antibody to rotavirus was detected in a child with cartilage hair hypoplasia. In cord bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

1988
1988
2004
2004

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
0
16
0
4
Order By: Relevance
“…rubella [34]. The high prevalence of rotavirus IgM seen in a previous study [19] was also explained by possible persistence of antibody although this was not apparent in other studies of infants [31] or adults [20].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…rubella [34]. The high prevalence of rotavirus IgM seen in a previous study [19] was also explained by possible persistence of antibody although this was not apparent in other studies of infants [31] or adults [20].…”
Section: Discussionmentioning
confidence: 79%
“…Studies which have investigated rotaviral infection in older age groups have long suggested that infection rates could be high, especially in case contacts [14,15]. Adult rotaviral infection has been measured using viral antigen in stools [16,17] and through serology using IgM as a marker of recent or current infection [18][19][20][21]. However, these studies did not consider seasonal variation which is normally considerable in most geographical settings except the tropics [22].…”
Section: Introductionmentioning
confidence: 99%
“…In 1988, Totterdell et al [9] were the first to utilize a lymphoproliferative assay to test T‐cell responses to rotavirus, when they observed cellular responses to rotavirus in various groups of adults. Offit et al.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the fact that the importance of humoral immune response in gastroenteric viral infections of porcine is well recognized (Corthesy and Kraehenbuhl, 1999;Saif et al, 1994;Tô et al, 1998;Van Cott et al, 1994;Yuan et al, 1996), little is known about cell-mediated immunity, particularly in PEDV infections. However, it has been proposed that cellular immune response may play an important role in the protection and recovery from infection, besides the fact that production of antibodies is regulated by cytokines produced by activated T lymphocytes and other mononuclear cells (Corthesy and Kraehenbuhl, 1999;Kraehenbuhl and Neutra, 1992;Saif, 1999;Totterdell et al, 1988).…”
Section: Introductionmentioning
confidence: 99%